Sex Offender Stigma: An Exploration of Vigilantism against Sex Offenders. Issue 2 (1st February 2019) - Cubellis, Michelle A.; Evans, Douglas N.; Fera, Adam G.
ABSTRACT: The current study compiles open-source news reports involving vigilantes who targeted individuals because of their status as a sex offender (SO) or their suspected involvement in a sex offense. The Sex Offender-Vigilante database includes 279 separate incidents of vigilantism against SOs, ranging from the dissemination of unsanctioned fliers to murder. Results indicate that the stigmatization that convicted SOs experience is so pervasive that it extends even to individuals suspected of having committed a sexual offense.